Developing a digital marketing–driven hybrid entrepreneurship model for wood waste craft MSMEs - Pipiet Mutiara Tri S; Taufik Rahman; Lidia Olga (International Journal of Applied Finance and Business Studies, 2026)
This study aims to design a hybrid entrepreneurship model based on digital marketing tailored to the needs of small-scale woodcraft MSMEs in rural areas. A mixed-methods approach was employed through a survey of 75 respondents and Focus Group Discussions (FGDs). The findings indicate that while entrepreneurs exhibit strong motivation and basic managerial capabilities, their digital literacy and use of online marketing channels remain limited. This reveals a readiness gap between intention and digital competence. In response, a conceptual model was formulated at Technology Readiness Level (TRL) 2, comprising four components: internal entrepreneurial readiness, integration of hybrid marketing channels (offline and online), mechanisms for training and mentoring, and strategic outcomes in the form of increased literacy and competitiveness. The model was developed modularly and grounded in field data, offering a framework for targeted interventions in training programs and policy design for digitally empowered MSME development.